Factors Affect Budget Absorption in Government Institutions of Indonesia, 2017 - Andriati, Reny (Universitas Muhammadiyah Yogyakarta, 2019)
The purpose of this research is to analyse and examine the effect of total budget, opinion of financial performance, corruption perception index, and performance accountability on the budget absorption in the Government Institutions. It is an associative-causal research. This research includes 66 government institutions which have complete dataset for research variables. The data were the secondary data in the form of financial publications of the government institutions in Indonesia. The hypotheses were tested with the multinomial linear regression analysis. The results of this research showed that, simultaneously, total budget, opinion of performance, corruption perception index, and performance accountability affected the budget absorption in government institutions. After the research was conducted and it was analysed statistically, only one variable were highly significant to the accumulation of budget absorption that is opinion of performance of a government institution.